2019
DOI: 10.21608/puj.2019.16532.1051
|View full text |Cite
|
Sign up to set email alerts
|

Modelling approaches to predict and evaluate schistosomiasis immunization utilizing SEA loaded on chitosan nanoparticles via liver tissue differentiation and angiogenesis

Abstract: Schistosomiasis is caused by blood flukes including all Schistosoma species. It affects about 207 million persons in 76 countries across the world, and is more prevalent in developing countries where about 800 million people are at the risk of schistosomiasis [1]. Following oviposition, schistosomes eggs that failed to exit with either urine or stools are carried back into the liver to be lodged in the pre-sinusoidal capillaries. The eggs are in intimate contact with the capillary endothelium before and during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
(51 reference statements)
1
3
0
Order By: Relevance
“…The combination of SLAP and SEA resulted in a significant reduction in egg count per gram of liver and intestine tissues (59% and 60.59%, respectively). Our results were in accordance with those of Etewa et al [9], who observed a significant reduction of S. mansoni eggs in the liver. Lower values were obtained by El-Ahwany et al [29], with 42.8% and 8.4% reduction of eggs in the liver and tissue, respectively.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The combination of SLAP and SEA resulted in a significant reduction in egg count per gram of liver and intestine tissues (59% and 60.59%, respectively). Our results were in accordance with those of Etewa et al [9], who observed a significant reduction of S. mansoni eggs in the liver. Lower values were obtained by El-Ahwany et al [29], with 42.8% and 8.4% reduction of eggs in the liver and tissue, respectively.…”
Section: Discussionsupporting
confidence: 94%
“…This indicates a good protective immune response to the combined vaccine in our study. In Etewa et al’s study [ 9 ], the liver sections of the SEA-vaccinated group had fewer numbers and smaller sizes of granuloma; degenerated ova surrounded by empty spaces were enclosed in fibrocellular granulomas in addition to mild lobular inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations